Left to right: labour market policy, labour market status and political affinities. (6th August 2018) - Meyer, Brett
Abstract: In recent decades, there has been a gradual decline in working-class organisations, including social democratic parties and trade unions, and an increase in support for populist radical right parties across western democracies. These trends have a plausible common cause: an increase in labour market insecurity associated with deindustrialisation may cause disenchantment with establishment organisations and support for politicians who criticise them. In this article, I examine how individual labour market status interacts with labour market policies to affect attitudes towards trade unions and populist radical right parties. I find that individuals with insecure employment status become less likely to support trade unions and more likely to support populist radical right parties as employment protection for secure workers increases. This effect is offset somewhat by spending on active labour market policies. I find evidence for these predictions in data for 27 Organisation for Economic Co-Operation and Development countries from 1995 to 2009.